STAD: Strategizing Training of Adult Learners through diversity / Faizah Abd Majid … [et al.] - Abd Majid, Faizah; Silah, Sumardianshah; Redzuan, Raiha Sharinaz; Mohd Shahrom, Syahreena; Shahril, Wan Nurul Elia Haslee (Research Innovation Business Unit, 2014)
In the 11th Malaysian Plan, the Prime Minister announced the urgent need for Malaysia to be driven by a strong economy based on innovation and creativity. The New Economic Model forged the strategies for the nation to aspire towards leveraging the economic chain through first class innovative and creative human capital. These needs have propelled professional training of the existing workforce and learning facilitation of the students in continuing or post-secondary education. Targeting the numerous trainers in any training institutions and academics in the higher education learning institutions, this project presents a comprehensive online module which focuses on the professional training and development of adult learners. The added value of this project are twofold; first it provides a holistic content coverage and second it suits professional development training and learning facilitation at the workplace and tertiary education respectively. Several theories underpin the development of this module namely; adult learning theories, self-directed learning theories, reflective teaching theories, and organizational training theories. The holistic content coverage is presented in a structured and orderly topics which comprise the following topics: a) Knowing your trainees and adult learners b) Playing your role as the trainer and learning facilitator c) Optimizing diversity among the trainees and adult learners d) Presenting training for impact through trainees’ diversity e) Providing engaging and active learning facilitation through learners’ diversity f) Assessing your training and facilitation impact While topics a, b, and c are general to either trainers or academics, topic d caters the needs of any trainers and topic e caters the need of any academics. This in itself ensures the practicality of the online module of two types of professional development; workplace training and academic learning. In describing the cosmetic and physicality aspects of the project, its accessibility via online facilities is an advantage. The presentation of the module in a user-friendly website encourages easy access regardless of time and place. The website is designed with the targeted audience in mind. Several related articles are provided as links enabling them easy downloading for their own training sessions. Besides the articles, there are also inventories which they could complete to gauge their strengths as trainers and learning facilitator. Best of all, all the articles and inventories are based on past research and most importantly, they have all been published in indexed journals. The testimonies of several potential users which were drawn from the market survey and pilot test of the website further confirm the reliability of the website: ‘STAD: Strategizing training of adult learners through diversity”. This part of the website content completes the holistic content coverage. This project has potential in its practicality and feasibility. Its practicality is determined by its holistic content coverage which focuses on real and meaningful use and transferability of training and learning facilitation ideas. Its feasibility is ensured by its appearance in a user-friendly website. Accessibility is ensured thus enabling a wide access and big number of users and visitors to the website. This in turn, promises good commercialization opportunities.